Prognostic value of a simple distance index derived from PET maximum intensity projection - Kargar Samani, Isaac; Gheysens, Olivier; Regnier, Maxime; Collard, Alix; André, Marc; Van Den Neste, Eric; Vander Borght, Thierry (Frontiers in Medicine, 2025)
IntroductionDissemination indices derived from [18F]FDG PET/CT, such as Dmax, Dmaxbulk, SPREADbulk, SPREADpatient, and DmaxVox are validated prognostic biomarkers in diffuse large B-cell lymphoma. We introduce DmaxVoxMIP, the distance between the outermost voxels of the two most distant lesions on a 2D maximum intensity projection image, which is easy and straightforward to obtain. Our goal is to evaluate DmaxVoxMIP’s prognostic value compared to other features for easier clinical application.MethodsMetabolic tumor volume and dissemination indices were obtained from LIFEx, while DmaxVoxMIP was obtained from Telemis and OsiriX.ResultsDmaxVoxMIP was not significantly higher in deceased than in living patients. However, patients with DmaxVoxMIP values above the derived cutoff showed a shorter survival. By combining MTV and DmaxVoxMIP, we obtained 3 risk groups for OS and PFS.DiscussionDmaxVoxMIP could advantageously replace other dissemination parameters as a prognostic index in patients with DLBCL.